Analysis of Blunt Abdominal Solid Organ Injury in Children: A Single Centre Study - Muhammad Riaz-Ul-Haq, Shafiq-Ur-Rehman, Yasir Makki, Sajid Mustafa, Shazia Siddique, Muhammad Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the management of solid organ injuries in blunt trauma abdomen (BTA) in children whether to conserve or operate. Study design: Descriptive case series. Place and duration of study: Department of Paediatric Surgery Sahiwal Teaching Hospital and Sahiwal Medical College Sahiwal from 1st January 2020 to 31st March 2022. Methodology: Fifty eight patients with blunt abdominal trauma due to any cause, the medical records of all patients with trauma of any kind age upto 13 years were carefully reviewed. Initial resuscitation was done according to ATLS protocol. Ultimate management decision was based on stability of patients after resuscitation. Results: The mean age was 5.34 years. Most of the patients suffered from road traffic accident, 50(86.2%). Fifty two (89.65%) patients showed free fluid in the abdomen. Organ injury in 27(46.55%) patients. CT abdomen with intravenous contrast confirmed findings of ultra sonography. Despite resuscitation, 17(43.9%) patients remained unstable and were operated. Forty one patients were kept on conservative treatment. Hospital stay ranged from 1-19 days. Conclusion: Although non-operative management is the treatment of choice in blunt trauma abdomen with solid organ injury but stability of the injured child is the central pivot around which the whole management revolves. Delay in presentation and failure of timely resuscitation results into high operative intervention. Keywords: Blunt trauma, solid, Liver, Spleen, children